Double-Blind Trial Assessing the Efficacy of Intravesical Therapy in Non– Muscle Invasive Bladder Cancer. A pathological guided perspective - Zeeshan Shaukat, Khawar Ali, Muhammad Haroon Ghous, Muhammad Nadeem Shafique, Mukhtiar Ahmed, Mehveen Iqbal, Muhammad Ali Sumbal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This randomized, double-blind, placebo-controlled trial aimed to evaluate the efficacy of intravesical therapy in patients with non–muscle invasive bladder cancer (NMIBC), utilizing pathological guidance for treatment stratification. A total of 200 patients diagnosed with intermediate- to high-risk NMIBC were enrolled and randomized into two groups: one receiving intravesical therapy and the other a placebo.